Self-Centered Function of Adaptive Immunity in Regulation of Immune Responses and in Tolerance - Silvana Balzar (Journal of Immunology Research)
The search for common mechanisms underlying the pathogenesis of chronic inflammatory conditions has crystalized the concept of continuous dual resetting of the immune repertoire (CDR) as a basic principle of the immune system function. Consequently, outlined was the first dynamic comprehensive picture of the immune system function. The goal of this study is to elaborate on regulation of immune responses and mechanisms of tolerance, particularly focusing on adaptive immunity. It is well established that the T/B cell repertoire is selected and maintained based on interactions with self. However, their activation also requires interaction with a self-specific major histocompatibility complex (MHC) “code,” i.e., the context of MHC molecules. Therefore, not only repertoire selection and maintenance but also the T/B cell activation and function are self-centered. Thus, adaptive effectors may be primarily focused on the state of self and maintenance of integrity of the self, and only to a certain degree on elimination of the foreign. As examples of such function are used immunologically poorly understood MHC-disparate settings typical for transplantation and pregnancy. Transplantation represents an extreme setting of strong systemic compartment-level adaptive/MHC-restricted immune responses. Described are clinically identified conditions for operational tolerance of MHC-disparate tissues/living systems in allotransplantation, which are in line with the CDR-proposed self-centered regulatory role of T/B cells. In contrast, normal pregnancy is coexistence of semiallogeneic or entirely allogeneic mother and fetus, but without alloreactivity akin to transplantation settings. Presented data support the notion that maintenance of pregnancy is a process that relies predominantly on innate/MHC-independent immune mechanisms. By the inception of hemotrophic stage of pregnancy (second and third trimester), both mother and child are individual living systems, with established adaptive immune repertoires. Although mother-fetus interactions at that point become indirect systemic compartment-level communications, their interactions throughout gestation remain within the innate realm of molecular-level adaptations.